2017
DOI: 10.1371/journal.pgen.1006917
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the meiotic recombination landscape and properties over a broad evolutionary distance in yeasts

Abstract: Meiotic recombination is a major factor of genome evolution, deeply characterized in only a few model species, notably the yeast Saccharomyces cerevisiae. Consequently, little is known about variations of its properties across species. In this respect, we explored the recombination landscape of Lachancea kluyveri, a protoploid yeast species that diverged from the Saccharomyces genus more than 100 million years ago and we found striking differences with S. cerevisiae. These variations include a lower recombinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(105 citation statements)
references
References 56 publications
12
91
2
Order By: Relevance
“…), and within genomes (e.g., Brion et al. ), these calculations should be considered a qualitative estimate of the recency of gene flow, and not a precise estimate of the time of admixture. Regardless of the precise age of admixture, the large size of the haplotypes indicates that hybridization occurred recently and rules out the possibility of retention of ancestral polymorphism (i.e., segregating variation that predates speciation).…”
Section: Resultsmentioning
confidence: 99%
“…), and within genomes (e.g., Brion et al. ), these calculations should be considered a qualitative estimate of the recency of gene flow, and not a precise estimate of the time of admixture. Regardless of the precise age of admixture, the large size of the haplotypes indicates that hybridization occurred recently and rules out the possibility of retention of ancestral polymorphism (i.e., segregating variation that predates speciation).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in a series of mlh3 point mutants showed a genome wide increase in non‐crossovers that supports a structural role for this complex in deciding the fate of meiotic recombination intermediates 56. Furthermore, recent studies in alternate yeast models such as Lachancea kluyveri hybrid have shed light on the significant inter‐specific variation in meiotic recombination frequency 57. Whole genome analysis of L. kluyveri meiotic spores revealed lower crossover frequencies compared to S. cerevisiae , a high proportion of non‐exchange chromosomes as well as a high frequency of 4:0 conversion tracts in the hybrid indicative of the role of abortive meiosis in genome evolution 57, 58.…”
Section: New Insights From Genome Wide Analysis Of Meiotic Recombinationmentioning
confidence: 87%
“…Furthermore, recent studies in alternate yeast models such as Lachancea kluyveri hybrid have shed light on the significant inter‐specific variation in meiotic recombination frequency 57. Whole genome analysis of L. kluyveri meiotic spores revealed lower crossover frequencies compared to S. cerevisiae , a high proportion of non‐exchange chromosomes as well as a high frequency of 4:0 conversion tracts in the hybrid indicative of the role of abortive meiosis in genome evolution 57, 58. These above mentioned studies are a few examples of the new insights into meiotic recombination mechanisms using genome wide recombination mapping methods.…”
Section: New Insights From Genome Wide Analysis Of Meiotic Recombinationmentioning
confidence: 99%
“…The study of meiotic recombination provided another good example of the relevance of exploring nonmodel species because little is known about variations of its properties across non‐ Saccharomyces species. Recombination rate is much lower in L. kluyveri than in S. cerevisiae , and recombination hotspots are not conserved between the two species (Brion et al, ). Another striking feature is the absence of recombination on the chromosome arm containing the MAT locus in L. kluyveri .…”
Section: Genomics Of Cladesmentioning
confidence: 99%
“…In fact, analysis revealed a relic of a 1‐Mb introgressed region with a different recombination and substitution regime compared with the rest of the genome. Interestingly, the gene expression landscape showed that genes located in this introgressed region tend to be less transcribed, have a higher variability between isolates, and are less involved in transcriptional networks (Brion et al, ).…”
Section: Population Genomics Of Nonconventional Yeastsmentioning
confidence: 99%